Analisis Level Kognitif Soal-Soal Pemecahan Masalah Pada Buku Siswa Matematika Kelas VII Kurikulum 2013 - Wahyuningsih, Takwatin; , Idris Harta, M.A, Ph.D (2016)
The aim of research is to analyze and describe problem solving item based on level of cognitive on Mathematic Student Book grade VII curriculum of 2013. The type of this research is descriptive qualitative. This research is done on even semester in academic year 2015/2016. The data of this study is problem solving items based on level of knowledge and comprehension, application, and reasoning. Technique of collecting data is content analysis and documentation, technique of analyze data are data reduction, data presentation, and conclusion. The result of this research shows that: 1) there are 33,70% problem solving items from 1730 items. 2) The dominant of Knowledge and comprehension level on problem solving items is Numerical aspect with 41,58%, level of Application on problem solving items is Algebra aspect with 6,18%, and level of Reasoning on problem solving items is Numerical aspect with 9,96%. 3) Percentage of Cognitives level on routine problem solving items is: level of Knowledge and comprehension with 52,75%, level of Application with 10,65%, and level of Reasoning with 6,70%. While the percentage of Cognitives level on non routine problem solving items is: level of Knowledge and comprehension with 17,87%, level of Application with 1,55%, and level of Reasoning with 10,48%.